1981
DOI: 10.1088/0034-4885/44/10/002
|View full text |Cite
|
Sign up to set email alerts
|

Clusters of galaxies

Abstract: During the last decade it was clearly established that the average mass-to-light ratio, (MIL), of galaxy clusters is much larger than that of the visible part of individual galaxies, which suggests the presence of missing mass in clusters. Flat outer rotation curves of individual spiral galaxies were discovered which led to the hypothesis of missing mass in galaxies in the form of dark massive haloes with an R-2 density distribution. But the R-3 density distribution of observed halo tracers, the large range in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 214 publications
0
9
0
Order By: Relevance
“…Faber & Gallagher 1979;Binggeli et al 1988;Giovanelli & Haynes 1991;Koo & Kron 1992;Ellis 1997), clusters of galaxies (e.g. Bahcall 1977;Rood 1981;Forman & Jones 1982;Bahcall 1988;Sarazin 1986), and active galactic nuclei (e.g. Rees 1984;Weedman 1986;Blandford et al 1990;Hartwick & Schade 1990;Warren & Hewett 1990;Antonucci 1993;Peterson 1997).…”
Section: Relevant Properties Of Lenses and Sourcesmentioning
confidence: 99%
“…Faber & Gallagher 1979;Binggeli et al 1988;Giovanelli & Haynes 1991;Koo & Kron 1992;Ellis 1997), clusters of galaxies (e.g. Bahcall 1977;Rood 1981;Forman & Jones 1982;Bahcall 1988;Sarazin 1986), and active galactic nuclei (e.g. Rees 1984;Weedman 1986;Blandford et al 1990;Hartwick & Schade 1990;Warren & Hewett 1990;Antonucci 1993;Peterson 1997).…”
Section: Relevant Properties Of Lenses and Sourcesmentioning
confidence: 99%
“…I begin with some qualitative considerations of the void phenomenon. Rood (1981) gives an excellent picture of the state of observational studies of galaxy clustering two decades ago. He remarks that 20 years earlier Mayall (1960, Fig. 3) had found that in the direction of the Coma Cluster, far more galaxies were in the cluster than the foreground.…”
Section: Introductionmentioning
confidence: 99%
“…For years, mass estimation of groups and clusters of galaxies has been one of the classical tasks of astronomers (see, for example : Zwicky 1933;Rood et al 1970;Gott & Turner 1977;Rood & Dickel 1978;Rood 1981;Huchra & Geller 1982;Geller 1984;Karachentsev 2005). Galactic kinematics, observations of X-rays from hot intra-cluster gas or gravitational lensing are some of the techniques used to infer the mass of these systems.…”
Section: Introductionmentioning
confidence: 99%